2014
DOI: 10.1016/j.rdc.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Environment, and Gene-Environment Interactions in the Development of Systemic Rheumatic Diseases

Abstract: Understanding disease susceptibility factors and gene-environment interactions may offer valuable insights into the biological mechanisms for the etiology of rheumatic diseases. Defining the contributions of genetic and environmental factors to the pathogenesis of rheumatic diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and ankylosing spondylitis (AS), may have important implications for understanding risk prediction, pathogenic mechanisms, cellular pathways, drug discovery, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 134 publications
1
50
0
1
Order By: Relevance
“…For example, several studies Kremeyer et al 2005;Zawicki and Witas 2008) have screened skeletal samples for the presence of an allele (CCR5D32) that confers resistance to HIV in living populations and also might have been beneficial during medieval plague outbreaks. Other studies have explored the genetic basis of specific skeletal pathologies, including rheumatoid arthritis (Korczowska 2014), ankylosing spondylitis (Sparks and Costenbader 2014), periodontal disease (Genco and Borgnakke 2013;Kang et al 2014), osteochondritis dissecans (Bates et al 2014), bone cancers (Kuehl and Bergsagel 2002;Mundy 2002;Prideaux et al 2014), and hundreds of inherited skeletal disorders (Warman et al 2011).…”
Section: Examination Of Frailty and Demographymentioning
confidence: 99%
“…For example, several studies Kremeyer et al 2005;Zawicki and Witas 2008) have screened skeletal samples for the presence of an allele (CCR5D32) that confers resistance to HIV in living populations and also might have been beneficial during medieval plague outbreaks. Other studies have explored the genetic basis of specific skeletal pathologies, including rheumatoid arthritis (Korczowska 2014), ankylosing spondylitis (Sparks and Costenbader 2014), periodontal disease (Genco and Borgnakke 2013;Kang et al 2014), osteochondritis dissecans (Bates et al 2014), bone cancers (Kuehl and Bergsagel 2002;Mundy 2002;Prideaux et al 2014), and hundreds of inherited skeletal disorders (Warman et al 2011).…”
Section: Examination Of Frailty and Demographymentioning
confidence: 99%
“…Furthermore, recent studies have shown that fibrotic ILD is characterized by an increased distal alveolar bacterial burden that might be responsible for both a rapidly deteriorating course of fibrotic disease and deadly ‘exacerbations' [29]. The establishment via new DNA sequencing technologies of the long-time hypothetic theory that a disturbed lung microbiome could trigger and/or aggravate tissue injury in susceptible pulmonary fibrosis patients bears significant importance for CTD patients not only for its role in the development and maintenance of lung disease but also for its potential pathogenetic role in manifestations of the mater disease [62,63,64]. …”
Section: Acute Lung Infections In Ctdsmentioning
confidence: 99%
“…Taking RA as an example, there are now 101 identified genetic loci associated with RA. Strikingly, these currently identified loci account for less than half the genetic risk, with the HLA shared epitope accounting for 12% and the non-HLA loci accounting for an additional 5% of the total variance (23). The missing heritability is thought to arise from several factors, including epigenetic changes, gene-environment interactions, rare genetic variants, and common variants with effect sizes below current detection limits (24).…”
Section: Discussionmentioning
confidence: 99%